2020
DOI: 10.4038/jccpsl.v26i2.8223
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of ‘Mother Supportive Group’ intervention on childhood nutrition improvement in Monaragala District of Sri Lanka

Abstract: Introduction: Effective, largescale, and nutrition-sensitive interventions addressing underlying determinants are required to accelerate progress in under-five nutrition. Objectives: To determine the effective coverage of Mother Supportive Group (MSG) intervention among its primary target population and its effectiveness in promotion of nutrition and growth of under-five children Methods: A descriptive, cross-sectional study was carried out among under-five children of Monaragala District. The study population… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 5 publications
0
2
0
Order By: Relevance
“…Accordingly, relevant activities or projects are undertaken to provide support to their own community. 2 Members of MSGs provide information, share experiences, advocate, and extend support to enable people to promote best practices in collaboration with health staff.…”
Section: What Are Mothers' Support Groups?mentioning
confidence: 99%
“…Accordingly, relevant activities or projects are undertaken to provide support to their own community. 2 Members of MSGs provide information, share experiences, advocate, and extend support to enable people to promote best practices in collaboration with health staff.…”
Section: What Are Mothers' Support Groups?mentioning
confidence: 99%
“…11 Another study by Gamagedara et al found that the contribution of MSGs (by creating awareness and health education) to children's attendance at growth monitoring programs and feeding during illness was statistically significantly higher than those who were not involved in MSG activities. 12 MSGs are also not the only communitybased program functioning at the village level in Sri Lanka. Many other community-based organizations, such as the Sarvodaya movement, operate in parallel with MSGs in some areas.…”
Section: The Mothers' Support Group Approach In Sri Lankamentioning
confidence: 99%